(3OjhGf eMeO GdCRQjs - (3eMeO GdQVG Hf eMeO GdGRQj GdHZOGOj,J (B1241 (3g` s ((3eMeO Hf GdTjN WGgQ GdSeGhj s)
(3ChdgG (B:s
(3bGd jeOM GdfHj GdeUWai Udi Gddg Ydjg hSde hjeOM GdTjN eMeO QVG GdfMhj dJNejSI ejeg GdHhUjQj CYbO LeGf bO JhbO QGFbI Ce GdfLe HGdBaGb bO Ye TGQbg s
(3BNQgG (B:s
(3bUjOI ddeDda jeOM hojgfF ajgG Bd YHjO, hHBNQ GdbUjOI HjJGf CMOgeG aGQSj hGdBNQ JQcj s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GfXQg eY OjhGf GdcYHjs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B313s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B199 s
Keywords: (3GdCOHs